Capturing The Invisible: Dynamics Of Abstraction And Extraction In Capitalism, Imperialism, And Photography Through The Lens Of R. F. Kuang’s Babel (2022) - Amal , Ben Niya; Najia , Omran (El Omda in Linguistics and Discourse Analysis, 2025)
This article examines the symbiotic relationship between capitalism and imperialism, as well as photography as a technology shaped by both, through an analysis of the dynamics of abstraction and extraction in R.F. Kuang’s Babel (2022). It covers key aspects of abstraction through insights from Marx’ Labour Theory of Value in addition to Said and Memmi’s insights on stereotypes as abstract generalizations. It examines the material history of photography and silver extraction in relation to capitalist free trade and imperialist expansion. The article concludes with an examination of the role of colonial discourse in abstracting the non-western “other” to fuel war sentiments and facilitate dominion and resource extraction.